Crack initiation life in notched Ti-6Al-4V titanium bars under uniaxial and multiaxial fatigue: synthesis based on the averaged strain energy density approach - Giovanni Meneghetti; Alberto Campagnolo; Filippo Berto; Keisuke Tanaka (Fracture and Structural Integrity)
The fatigue behaviour of circumferentially notched specimens made of titanium alloy, Ti-6Al-4V, has been analysed. To investigate the notch effect on the fatigue strength, pure bending, pure torsion and multiaxial bending-torsion fatigue tests have been carried out on specimens characterized by two different root radii, namely 0.1 and 4 mm. Crack nucleation and subsequent propagation have been accurately monitored by using the direct current potential drop (DCPD) technique. Based on the results obtained from the potential drop technique, the crack initiation life has been defined in correspondence of a relative potential drop increase ?V/?V0 equal to 1%, and it has been used as failure criterion. Doing so, the effect of extrinsic mechanisms operating during crack propagation phase, such as sliding contact, friction and meshing between fracture surfaces, is expected to be reduced. The experimental fatigue test results have been re-analysed by using the local strain energy density (SED) averaged over a structural volume having radius R0 and surrounding the notch tip. Finally, the use of the local strain energy density parameter allowed us to properly correlate the crack initiation life of Ti-6Al-4V notched specimens, despite the different notch geometries and loading conditions involved in the tests.